Amide Proton Transfer Weighted MR Imaging for Predicting Meningioma Stiffness: A Feasibility Study. Issue 4 (5th August 2022) - Yu, Hao; Zhu, Laimin; Wang, Yanting; Yue, Xiuzheng; Wang, Weiwei; Sun, Zhanguo; Jiang, Shanshan; Chen, Yueqin; Wen, Zhibo
Abstract : Background: Stiffness of meningioma is an important factor affecting the surgical resection and the prognosis of patients. Purpose: To examine the feasibility of APTw‐magnetic resonance imaging (MRI) in evaluating meningioma stiffness. Study Type: Retrospective. Population: Seventy‐one patient with meningiomas, 39 were male and 32 were female; the mean age was 51 ± 10 years. Field Strength/Sequence: 3.0T; Turbo‐spin‐echo T1 ‐weighted and Gd‐T1 ‐weighted sequence; Turbo‐spin‐echo T2 ‐weighted sequence; 2D fat‐suppressed, turbo‐spin‐echo APTw pulse sequence. Assessment: The T1 WI signal intensity score, T2 WI signal intensity score, APTwmin, APTwmax, and APTwmean values were compared between soft, medium stiff and stiff meningiomas or non‐stiff meningiomas and stiff meningiomas group. Statistical Tests: Chi‐square test, one‐way ANOVA analysis, independent‐samples t ‐test, intra‐class correlation coefficient, rank‐sum test, receiver operating characteristic curve analysis. P < 0.05 was considered statistically significant in all tests. Results: APTwmin and APTwmean in the stiff group were significantly lower than that in the non‐stiff group (2.79% ± 0.42% vs. 1.90% ± 0.60% and 3.20% ± 0.31% vs. 2.55% ± 0.61%). APTwmin and APTwmean in the stiff group were significantly lower than that in the medium stiff and soft groups (1.90% ± 0.60% vs. 2.69% ± 0.40% and 3.12% ± 0.32%, 2.55% ± 0.61% vs. 3.17% ± 0.33% and 3.39% ± 0.18%), APTwmin in the medium stiff group was significantly lower than in the soft group, there was no significant difference in APTwmean between the medium stiff and soft groups ( P = 0.190). APTwmin showed the best diagnostic performance for evaluating meningioma stiffness with an area under the curve of 0.913, when the APTwmin was lower than 2.4%, the meningioma was defined as a stiff tumor, the sensitivity, specificity, and accuracy were 87.1%, 87.5%, and 85.9%, respectively. Data Conclusion: APTw‐MRI could be used to evaluate meningioma stiffness, with APTwmin having the best evaluative efficiency. Level of Evidence: 3 Technical Efficacy: Stage 1